Penerapan Teknologi Venturi Finebubble Portable Buoy Berbasis Solar Cell dan Internet Of Things Pada Tambak Udang Vaname Karangrejo Banyuwangi - Achmad Noval Kurniawan Raroeng; Moch. Yusron; Alfan Mubarok; Siti Ainun Fiqiyah; Anfasa Syahrul Habibie; Risse Entikaria Rachmanita (Journal of Community Development, 2023)
Indonesia is a maritime country that has enormous potential in marine products. One of the marine products which is the highest export commodity is shrimp. Lingkungan Pakem, Karangrejo Village, Banyuwangi Regency is a partner location that is one of the national shrimp producing centers. Partners cultivate vaname shrimp with an intensive system as a producer of oxygen bubbles. The application of an intensive system causes problems, namely the amount of electricity costs and the uneven flow of water flow so that oxygen levels are not optimal. Based on these problems, the application of venturi finebubble portable buoy technology based on solar cells and IoT aims to increase the efficiency of the production of vannamei shrimp produced. The stages of technology application to partners consist of observation, planning, manufacture, assembly, and evaluation. The implementation of this technology can reduce electricity bills from operational costs in one harvest period (2 months) which was initially IDR 3,000,000.00 to IDR 2,000,000.00 and the average mortality rate of shrimp from 3000 individuals is equivalent to IDR 1,100,000.00 to 1560 individuals which is equivalent to IDR 572,000.00. Thus, the savings achieved are 37% or IDR 1,528,000.00 per harvest.